The test method of a new alkali-silica reaction prevention technology - Ong Frank; Farleman Bailey; Seiler Paul (MATEC Web of Conferences)
Alkali–silica reaction (ASR) is a major concrete durability problem. The occurrence of ASR results in significant maintenance and reconstruction costs to concrete infrastructures all over the world. Current market solutions for preventing ASR are not always sustainable, such as hauling non-reactive aggregates or fly ash from a long distance; or using of Li-based chemical admixture that is facing the challenge of raw material’s availability. The current article will present an ASR preventing technical solution, which is based on the abundant soluble Ca2+ ions. However, the current ASTM C1567 [1] test method is not suitable for assessing the effectiveness of this new ASR preventing technology due to the leaching of soluble Ca2+ ions into the soak solution. Two new ASR expansion test methods have been developed to address the leaching issue: (1) single mortar bar in sealed pipe with 10 mL H2O and additional NaOH in mortar, and (2) ASTM C1567 with additional Ca2+ in soak solution to buffer leaching. The effect of ASR prevention of this innovative technology was evaluated and compared with these two new test methods for mortars made with several ASR reactive aggregates. The ASTM C1567 with additional Ca2+ in soak solution was selected as the test method for the assessment of the new ASR-preventing technology based on soluble Ca2+ ions.